Tungsten disulfide nanotubes enhance flow-induced crystallization and radio-opacity of polylactide without adversely affecting in vitro toxicity. (15th January 2022) - Ramachandran, Karthik; Shao, Zixuan; Di Luccio, Tiziana; Shen, Bo; Bello, Edgar E. Ruiz; Tammaro, Loredana; Villani, Fulvia; Loffredo, Fausta; Borriello, Carmela; Di Benedetto, Francesca; Magee, Eimear; McNally, Tony; et al.
Abstract: Treatment of vascular disease, from peripheral ischemia to coronary heart disease (CHD), is poised for transformation with the introduction of transient implants designed to "scaffold" regeneration of blood vessels and ultimately leave nothing behind. Improved materials could expand the use of these devices. Here, we examine one of the leading polymers for bioresorbable scaffolds (BRS), polylactide (PLA), as the matrix of nanocomposites with tungsten disulfide (WS2 ) nanotubes (WSNT), which may provide mechanical reinforcement and enhance radio-opacity. We evaluate in vitro cytotoxicity using vascular cells, flow-induced crystallization and radio-opacity of PLA-WSNT nanocomposites at low WSNT concentration. A small amount of WSNT (0.1 wt%) can effectively promote oriented crystallization of PLA without compromising molecular weight. And radio-opacity improves significantly: as little as 0.5 to 1 wt% WSNT doubles the radio-opacity of PLA-WSNT relative to PLA at 17 keV. The results suggest that a single component, WSNT, has the potential to increase the strength of BRS to enable thinner devices and increase radio-opacity to improve intraoperative visualization. The in vitro toxicity results indicate that PLA-WSNT nanocomposites are worthy of investigation in vivo . Although substantial further preclinical studies are needed, PLA-WSNT nanocomposites may provide a complement of material properties that may improve BRS and expand the range of lesions that can be treated using transient implants. Statement of significance: Bioresorbable Scaffolds (BRSs) support regeneration of arteries without permanent mechanical constraint. Poly-L-lactide (PLLA) is the structural material of the first approved BRS for coronary heart disease (ABSORB BVS), withdrawn due to adverse events in years 1-3. Here, we examine tungsten disulfide (WS2 ) nanotubes (WSNT) in PLA to address two contributors to early complications: (1) reinforce PLLA (enable thinner BRS), and (2) increase radiopacity (provide intraoperative visibility). For BRS, it is significant that WSNT disperse, remain dispersed, reduce friction and improve mechanical properties without additional chemicals or surface modifications. Like WS2 nanospheres, bare WSNT and PLA-WSNT nanocomposites show low cytotoxicity in vitro . PLA-WSNT show enhanced flow-induced crystallization relative to PLA, motivating future study of the processing behavior and strength of these materials. Graphical abstract: Image, graphical abstract